Effects of Design Features of Explicit Values Clarification Methods: A Systematic Review. (August 2016) - Witteman, Holly O.; Gavaruzzi, Teresa; Scherer, Laura D.; Pieterse, Arwen H.; Fuhrel-Forbis, Andrea; Chipenda Dansokho, Selma; Exe, Nicole; Kahn, Valerie C.; Feldman-Stewart, Deb; Col, Nananda F.; Turgeon, Alexis F.; Fagerlin, Angela
Background. Diverse values clarification methods exist. It is important to understand which, if any, of their design features help people clarify values relevant to a health decision.Purpose. To explore the effects of design features of explicit values clarification methods on outcomes including decisional conflict, values congruence, and decisional regret.Data Sources. MEDLINE, all EBM Reviews, CINAHL, EMBASE, Google Scholar, manual search of reference lists, and expert contacts.Study Selection. Articles were included if they described the evaluation of 1 or more explicit values clarification methods.Data Extraction. We extracted details about the evaluation, whether it was conducted in the context of actual or hypothetical decisions, and the results of the evaluation. We combined these data with data from a previous review about each values clarification method's design features.Data Synthesis. We identified 20 evaluations of values clarification methods within 19 articles. Reported outcomes were heterogeneous. Few studies reported values congruence or postdecision outcomes. The most promising design feature identified was explicitly showing people the implications of their values, for example, by displaying the extent to which each of their decision options aligns with what matters to them.Limitations . Because of the heterogeneity of outcomes, we were unable to perform a meta-analysis. Results should be interpreted with caution.Conclusions . Few values clarification methods have been evaluated experimentally. More research is needed to determine effects of different design features of values clarification methods and to establish best practices in values clarification. When feasible, evaluations should assess values congruence and postdecision measures of longer-term outcomes.